DMPP nitrification inhibitor in the fertilization of forage corn in the Comarca Lagunera - García Sepúlveda, Jorge Luis; Cueto Wong, José Antonio; Figueroa Viramontes, Uriel; Reta Sánchez, David Guadalupe (Revista Mexicana de Ciencias Agrícolas, 2019)
The Comarca Lagunera produces more than 2 343 million liters of milk per year from a herd of more than 465 thousand head of dairy cattle. The contamination of groundwater by nitrates and the emission of greenhouse gases (NO2) are the most serious major environmental problems in intensive agriculture. The objective of this research was to evaluate the effect of fertilizers with nitrification inhibitor on yield, forage quality and foliar nutritional concentration. The research was conducted in 2017 at the La Laguna Experimental Field (INIFAP). Five fertilization programs with and without DMPP nitrification inhibitor plus a regional control with conventional fertilization were evaluated. The treatment that received 240 kg N ha-1 (regional control) produced the highest yield in green forage and dry matter (41.5 t ha-1 and 13.88 t DM ha-1 respectively). However, these values were statistically equal to the dose of 120 kg N ha-1 + IN DMPP. The highest grain yield (6.05 t ha-1) was achieved with the treatment of 240 kg of N ha-1 + IN DMPP. The highest concentration of N in the foliage (2.43 and 2.32%) was achieved with the highest doses of N (360 kg ha-1) without DMPP IN and with MPP IN respectively. Regarding the foliar nutritional concentration of Mg, S, Fe and Zn there was no significant difference between treatments. Forage quality analyzes indicate that the highest crude protein content (8.95%) was recorded with the 360 kg treatment of N ha-1 + IN DMPP. It is concluded that fertilizers with nitrification inhibitor can reduce the doses of N in feed corn.